Engaging Pharmacy Students, Residents, and Fellows in Antimicrobial Stewardship. (December 2015) - Chahine, Elias B.; El-Lababidi, Rania M.; Sourial, Mariette
Antimicrobial stewardship programs are mainly established by infectious diseases physicians and infectious diseases-trained clinical pharmacists with the goal of optimizing patients' outcomes while halting antimicrobial resistance, decreasing adverse events, and controlling health care cost. The role of the infectious diseases-trained clinical pharmacist in antimicrobial stewardship is well established; however, there are not enough formally trained pharmacists to assume the challenging responsibilities of the steward coordinator. The purpose of this article was to review the available literature and resources and propose a model to engage introductory pharmacy practice experience students, advanced pharmacy practice experience students, postgraduate year (PGY) 1 pharmacy residents, PGY2 infectious diseases pharmacy residents, and PGY2 or PGY3 infectious diseases pharmacy fellows in antimicrobial stewardship. Further studies are needed to assess and document the impact of pharmacy students and postgraduate trainees on antimicrobial stewardship programs.